Stabilization of organic material from soils and soil-like bodies in the Lena River Delta (13C-NMR spectroscopy analysis) - Polyakov, Vyacheslav; Abakumov, Evgeny (Spanish journal of soil science, 2020)
The Arctic ecosystem has a huge reservoir of soil organic carbon stored in permafrost-affected soils and biosediments. During the short vegetation season, humification and mineralization processes in the active soil layer result in the formation of specific soil organic substances – humic substances. Humic acids are high molecular, specific, thermodynamically stable macromolecules. The study was conducted in the Lena River Delta, the largest river delta located in the Arctic. Cryosol-type soils on alluvial deposits of the river form an area of about 45 thousand km2 under permafrost conditions. The vegetation cover is represented by moss-lichen communities with the presence of Salix glauca in the flooded areas, as well as Betula nana in the areas not subject to flooding. The paper presents the elemental and molecular composition of humic acids isolated from soils, integral indicators of humification (stabilization) of organic matter in the soils of the Lena River Delta. The study was conducted using the 13C (CP/MAS) NMR spectroscopy method. In the work, it was revealed that up to 33% of aromatic and up to 15% COOR fragments are accumulated in humic acids. The AR/AL ratio ranged from 0.69 to 0.89. The studied soils are variants of modern soil formation (not subjected to alluvial processes) and soil-like bodies that melted from the IC of the river delta. A relatively high degree of condensation of humic acid macromolecules in comparison with other polar regions of the Arctic and Antarctic was noted.